Weight-reducing Effect of Diguanides in Obese Non-diabetic Women. Issue 5648 (5th April 1969) - Munro, J. F.; MacCuish, A. C.; Marshall, A.; Wilson, Elizabeth M.; Duncan, L. J. P.
Abstract : A double-blind trial was carried out to assess the weight-reducing effect of the diguanides in 90 women with refractory obesity and normal oral glucose tolerance. The daily dosage of phenformin and metformin was increased at weekly intervals up to 300 mg. and 3 g. respectively, and patients were maintained at this dose or on the maximum they could tolerate without anorexia or other gastrointestinal side-effects. Seventy-seven completed the 16-week period of study. There was a statistically significant difference between the mean weight change of the control and the treated groups, but no difference between those treated by phenformin or metformin. The weight-losing influence of the diguanides appeared to be no longer significant after the twelfth week of treatment.